2016
DOI: 10.1097/ijg.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Intraocular Pressure Between Both Eyes After Bilateral Selective Laser Trabeculoplasty in Open-angle Glaucoma

Abstract: There is a strong and significant correlation in the IOP-lowering response to SLT between both eyes in near 80% of treated OAG subjects, whereas near 20% had an asymmetrical and inverse response to SLT between both the eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…26 In addition, Lee et al demonstrated that IOP response in both eyes was correlated after bilateral SLT. 27 In our study, we also demonstrated that significant correlations of both IOP responses to SLT exist at 1 month and 6 months postoperative. We speculated that this might be because both eyes have similar function and TM structure.…”
Section: Volume 6 | Number 1 2017supporting
confidence: 76%
“…26 In addition, Lee et al demonstrated that IOP response in both eyes was correlated after bilateral SLT. 27 In our study, we also demonstrated that significant correlations of both IOP responses to SLT exist at 1 month and 6 months postoperative. We speculated that this might be because both eyes have similar function and TM structure.…”
Section: Volume 6 | Number 1 2017supporting
confidence: 76%
“…Previous studies suggest that SLT has a greater effect when higher energy (Ayala & Chen ) and a greater amount of laser spots (Lee et al. ) are used during the procedure. Since we found no difference between residents and specialists, who used the same treatment regime, but a significant difference between these groups and senior specialists who used more laser spots and energy during treatment, the data would suggest that experience is not the deciding factor in terms of outcome and IOP reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, if success was achieved in one eye but not in the fellow eye, there was strong negative correlation between the two eyes. In the majority of eyes, the success or non-success of one eye may predict the clinical outcome of the fellow eye [32]. …”
Section: Surgical Techniquementioning
confidence: 99%